Notes from Underground: Are Cognitive-Enhancing Drugs Respecting their Promises? - Larøi, Frank; Raballo, Andrea (Frontiers in Psychology, 2010)
Cognitive deficits are increasingly acknowledged as a highly relevant clinical feature of schizophrenia, susceptible of therapeutic intervention. Considerable efforts have been devoted to identify and develop pharmacological agents that provide cognitive-enhancing benefits to patients with schizophrenia. However, results from studies are not univocal and the “real world” cognitive functioning gain provided by these agents seems disappointingly modest. Three issues are crucial in this respect. First, there is no convincing evidence that atypical agents are any better than typical agents in improving cognitive functioning. Second, even though studies observe statistically significant treatment effects on cognition, these gains are poor or imperceptible on a clinical and functional level. Third, studies do not report differences in treatment effect compared to placebo effect in terms of their cognitive enhancing effects. Finally, examples of interventions that do provide important and meaningful improvements in cognitive functioning in schizophrenia patients will be briefly presented.